2009
DOI: 10.1590/s1517-83822009000400032
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of recombinant MSP5 Anaplasma marginale Havana isolate

Abstract: ABSTRACTprotein was recognized by the monoclonal antibody ANAF16C1 and it showed a high similitude percent with the gene sequence described for other Anaplasma marginale isolates. These data are very important for the development of a diagnostic test for A. marginale using the MSP5 recombinant protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In the prediction, we found that all 36 UdLAMPs have conformational and linear epitopes for B lymphocytes and are predicted as antigenic (VaxiJen predictor). A considerable number of regions of conformational and linear epitopes were greater than or equal to the values for Msp5, one of the main surface proteins of A. marginale, known for its ability to induce antibody production during cattle infection [14]. The presence of these epitopes points to these molecules as agents capable of stimulating the development of a humoral immunological response.…”
Section: Discussionmentioning
confidence: 99%
“…In the prediction, we found that all 36 UdLAMPs have conformational and linear epitopes for B lymphocytes and are predicted as antigenic (VaxiJen predictor). A considerable number of regions of conformational and linear epitopes were greater than or equal to the values for Msp5, one of the main surface proteins of A. marginale, known for its ability to induce antibody production during cattle infection [14]. The presence of these epitopes points to these molecules as agents capable of stimulating the development of a humoral immunological response.…”
Section: Discussionmentioning
confidence: 99%